New insights into the nature of the peculiar star θ Carinae - Hubrig, S. (2008)
θ Context. Carinae belongs to a group of peculiar early-type stars (OBN) with enhanced nitrogen and carbon deficiency. It is also known as a binary system, but it is not clear yet whether the chemical anomalies can be explained by mass transfer between the two components. On the basis of the previously reported spectral variability of a few metal lines it may be expected that Car possesses a weak magnetic field.Aims. A study of the physical nature of this hot massive binary which is furthermore a well-known blue straggler lying ~2 mag above the turnoff of the young open cluster IC 2602 is important to understand the origin of its strong chemical anomalies.Methods. We acquired high resolution spectroscopic and low resolution spectropolarimetric observations to achieve the following goals: a) to improve the orbital parameters to allow a more in-depth discussion on the possibility of mass transfer in the binary system; b) to carry out a non-local thermodynamic equilibrium (NLTE) abundance analysis; and c) to search for the presence of a magnetic field. Results. The study of the radial velocities using CORALIE spectra allowed us to significantly improve the orbital parameters. A comparative NLTE abundance analysis was undertaken for Car and two other early B-type stars with recently detected magnetic fields, τ Sco and ξ1 CMa. The analysis revealed significantly different abundance patterns: a one-order-of-magnitude nitrogen overabundance and carbon depletion was found in Car, while the oxygen abundance is roughly solar. For the stars ξ1 CMa and τ Sco the carbon abundance is solar and, while an N excess is also detected, it is of much smaller amplitude (0.4-0.6 dex). Such an N overabundance is typical of the values already found for other slowly-rotating (magnetic) B-type dwarfs. For Car, we attribute instead the chemical peculiarities to a past episode of mass transfer between the two binary components. The results of the search for a magnetic field using FORS 1 at the VLT consisting of 26 measurements over a time span of ~1.2 h are rather inconclusive: only few measurements have a significance level of 3. Although we detect a periodicity of the order of ~8.8 min in the dataset involving the measurements on all hydrogen Balmer lines with the exception of the Hα and H lines, these results have to be confirmed by additional time-resolved magnetic field observations.